Influence estimation of conic evolvent transmissions parameters on their longevity and wear. P. 2. Transmissions with oblique teeth - Чернець, М.В.; Береза, В.В.; Чернець, Ю.М. (Problems of Tribology, 2014)
It is set for the oblique teeth conical transmissions of conformity to the law of influencing of the module of restriction and transmission relation on maximal contact tisci, resource of transmission, wear of teeth that speed of sliding in the restriction. The results of researches for their show evidently are given graphicly.